Cover Image, Volume 37, Issue 8. Issue 8 (11th July 2016) - Vitellius, Géraldine; Fagart, Jérôme; Delemer, Brigitte; Amazit, Larbi; Ramos, Nelly; Bouligand, Jérôme; Le Billan, Florian; Castinetti, Frédéric; Guiochon‐Mantel, Anne; Trabado, Séverine; Lombès, Marc
Abstract : On the cover : The cover image, by Marc Lombes et al., is based on the Research Article Three Novel Heterozygous Point Mutations of NR3C1 Causing Glucocorticoid Resistance, Pages 794–803, DOI:10.1002/humu.23008 .